Principal leadership training in building a cohesive school climate - Rasyid, Ramli; Natsir, Taufiq; Ishak, Ishak; Ridwan, Ridwan; Wahidiyat Haedar, Ahmad (Jurnal Hasil Inovasi Masyarakat, 2025)
Principal leadership training is one of the strategic efforts to improve the quality of governance and organizational climate in educational units. This community service activity was carried out at SMKN 5 Majene with the aim of equipping the principal and school management team in building a cohesive and communicative school climate. The training method used combines transformative leadership theory with a participatory approach through discussions, case studies, and simulations. Participants consisting of school principals, vice principals, and representative teachers participated in a series of activities for two days. Evaluation was carried out using pre-test and post-test as well as reflective questionnaires to measure changes in participants' understanding and behavior. The results of the training showed an increase in the average score of participants from 58.3 in the pre-test to 85.1 in the post-test, indicating the success of knowledge and skills transfer. In addition, there has been a significant change in teachers' communication patterns and involvement in decision-making, which supports the formation of a more open and collaborative work climate. The implementation of follow-up plans such as the establishment of the School Internal Communication Forum and weekly reflection sessions are clear evidence of the school's commitment to maintaining the sustainability of these changes. This activity makes an important contribution in strengthening the capacity of school leadership as a key factor in improving the quality of education and providing an applicative and contextual training model for other schools.